The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1103/physrevapplied.13.044034
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial N Vacancies in GaN /( Al<

Abstract: We show that N-polar GaN/(Al, Ga)N/GaN heterostructures exhibit significant N deficiency at the bottom (Al, Ga)N/GaN interface, and that these N vacancies are responsible for the trapping of holes observed in unoptimized N-polar GaN/(Al, Ga)N/GaN high electron mobility transistors. We arrive at this conclusion by performing positron annihilation experiments on GaN/(Al, Ga)N/GaN heterostructures of both N and Ga polarity, as well as state-of-the-art theoretical calculations of the positron states and positronel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In the fast positron setup, a high-purity Ge (HPGe) detector with energy resolution of 1.15 keV at 511 keV was used to record the annihilation photons emitted from two sample pieces with a positron source sandwiched in between. The positron source with 1 MBq of activity was composed of 22 Na encapsulated in 1.5-μm-thick Al-foil. The amount of source annihilations was determined with positron lifetime measurements to be less than 4%.…”
Section: A Sample Orientation In Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fast positron setup, a high-purity Ge (HPGe) detector with energy resolution of 1.15 keV at 511 keV was used to record the annihilation photons emitted from two sample pieces with a positron source sandwiched in between. The positron source with 1 MBq of activity was composed of 22 Na encapsulated in 1.5-μm-thick Al-foil. The amount of source annihilations was determined with positron lifetime measurements to be less than 4%.…”
Section: A Sample Orientation In Experimentsmentioning
confidence: 99%
“…Positron annihilation spectroscopy is a nondestructive method with selective sensitivity to neutral and negative vacancy-type defects, and second-order sensitivity to negatively charged defects without open volume [11]. Thanks to these properties, positron annihilation methods have been successful in identifying the role of native point defects in the electrical compensation of n-type doped compound semiconductors such as GaN, ZnO, AlN, InN, and In 2 O 3 [12][13][14][15][16], as well as their alloys such as InGaN and AlGaN [17][18][19][20][21][22]. In spite of the otherwise significant research interest in β-Ga 2 O 3 , the number of reported studies with positron annihilation is surprisingly low [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…[ 61 ] This phenomenon has been very recently utilized to study the atomic‐scale structure of the hole‐attractive interface in N‐polar high electron mobility transistor (HEMT) devices. [ 63 ] Interestingly, the strong 2D confinement caused by the built‐in electric fields enhances the positron sensitivity also to N vacancies that are otherwise essentially invisible to positron annihilation methods, as shown in Figure . This finding opens up new opportunities for using positron annihilation spectroscopy for studying defects and carrier localization phenomena in devices and device‐like heterostructures.…”
Section: Iii‐nitride Alloys and Heterostructuresmentioning
confidence: 99%
“…The experimental "MQW" data are from a specifically designed multiquantum-well structure where positrons annihilate at the interface(s) of interest, showing good agreement with calculated curves for 2-4 V N . Reproduced with permission [63]. Copyright 2020, American Physical Society.…”
mentioning
confidence: 99%
“…This trend is similar to what has been observed previously in Si-doped AlGaN with 60% Al, 22 while generally from the point of view of electrical compensation, Si doping has not been found to induce high concentrations of cation vacancies in GaN or AlGaN up to 65% Al content. 20,[22][23][24][25][26] It is known that in GaN, 8,27 and particularly in AlN, 10 negative non-open volume defects (negative ions) can effectively trap positrons also at room temperature due the relatively high binding energy of this shallow trap. Trapping at these negative ions produces (S, W) parameters of the lattice and limits the effect of the trapping to cation vacancies on the annihilation parameters.…”
mentioning
confidence: 99%